A case of musical preference for Johnny Cash following deep brain stimulation of the nucleus accumbens - Mantione, Mariska; Figee, Martijn; Denys, Damiaan (Frontiers in Behavioral Neuroscience, 2014)
Music is among all cultures an important part of the live of most people. Music has psychological benefits and may generate strong emotional and physiological responses. Recently, neuroscientists have discovered that music influences the reward circuit of the nucleus accumbens, even when no explicit reward is present. In this clinical case study, we describe a 60-year old patient who developed a sudden and distinct musical preference for Johnny Cash following deep brain stimulation targeted at the nucleus accumbens for treatment-refractory obsessive-compulsive disorder. This case report substantiates the assumption that the nucleus accumbens is involved in musical preference, based on the observation of direct stimulation of the accumbens with deep brain stimulation. It also shows that accumbens DBS can change musical preference without habituation of its rewarding properties.